Characterization of Genetic Diversity in the Nematode Pristionchus pacificus from Population-Scale Resequencing Data. Issue 4 (1st April 2014) - Rödelsperger, Christian; Neher, Richard A; Weller, Andreas M; Eberhardt, Gabi; Witte, Hanh; Mayer, Werner E; Dieterich, Christoph; Sommer, Ralf J
Abstract: The hermaphroditic nematode Pristionchus pacificus is an established model system for comparative studies with Caenorhabditis elegans in developmental biology, ecology, and population genetics. In this study, we present whole-genome sequencing data of 104 P. pacificus strains and the draft assembly of the obligate outcrossing sister species P. exspectatus . We characterize genetic diversity within P. pacificus and investigate the population genetic processes shaping this diversity. P. pacificus is 10 times more diverse than C. elegans and exhibits substantial population structure that allows us to probe its evolution on multiple timescales. Consistent with reduced effective recombination in this self-fertilizing species, we find haplotype blocks that span several megabases. Using the P. exspectatus genome as an outgroup, we polarized variation in P. pacificus and found a site frequency spectrum (SFS) that decays more rapidly than expected in neutral models. The SFS at putatively neutral sites is U shaped, which is a characteristic feature of pervasive linked selection. Based on the additional findings (i) that the majority of nonsynonymous variation is eliminated over timescales on the order of the separation between clades, (ii) that diversity is reduced in gene-rich regions, and (iii) that highly differentiated clades show very similar patterns of diversity, we conclude that purifying selection on many mutations with weak effects is a major force shaping genetic diversity in P. pacificus .